Epigenetics/epigenomics and prevention by curcumin of early stages of inflammatory‐driven colon cancer. Issue 2 (9th December 2019) - Wu, Renyi; Wang, Lujing; Yin, Ran; Hudlikar, Rasika; Li, Shanyi; Kuo, Hsiao‐Chen D.; Peter, Rebecca; Sargsyan, Davit; Guo, Yue; Liu, Xia; Kong, AN
Abstract: Colorectal cancer (CRC) is associated with significant morbidity and mortality in the US and worldwide. CRC is the second most common cancer‐related death in both men and women globally. Chronic inflammation has been identified as one of the major risk factors of CRC. It may drive genetic and epigenetic/epigenomic alterations, such as DNA methylation, histone modification, and non‐coding RNA regulation. Current prevention modalities for CRC are limited and some treatment regimens such as use the nonsteroidal anti‐inflammatory drug aspirin may have severe side effects, namely gastrointestinal ulceration and bleeding. Therefore, there is an urgent need of developing alternative strategies. Recently, increasing evidence suggests that several dietary cancer chemopreventive phytochemicals possess anti‐inflammation and antioxidative stress activities, and may prevent cancers including CRC. Curcumin (CUR) is the yellow pigment that is found in the rhizomes of turmeric ( Curcuma longa) . Many studies have demonstrated that CUR exhibit strong anticancer, antioxidative stress, and anti‐inflammatory activities by regulating signaling pathways, such as nuclear factor erythroid‐2‐related factor 2, nuclear factor‐κB, and epigenetics/epigenomics pathways of histones modifications, and DNA methylation. In this review, we will discuss the latest evidence in epigenetics/epigenomics alterations by CUR in CRC and their potential contribution in the prevention of CRC.